Manusia dalam alqur’an : al-basyar, al-ins, al-insan - Ahmad Farid; Nina Ludiana; Putri Balahaqis Eliqa (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The Qur'an describes humans using various terms, including